2012
DOI: 10.2478/v10176-012-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modelling of Lovastatin Biosynthesis by Aspergillus Terreus Cultivated on Lactose and Glycerol as Carbon Sources

Abstract: A kinetic model to describe lovastatin biosynthesis by Aspergillus terreus ATCC 20542 in a batch culture with the simultaneous use of lactose and glycerol as carbon sources was developed. In order to do this the kinetics of the process was first studied. Then, the model consisting of five ordinary differential equations to balance lactose, glycerol, organic nitrogen, lovastatin and biomass was proposed. A set of batch experiments with a varying lactose to glycerol ratio was used to finally establish the form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…All in all, it is unlikely to find in literature the exponential growth curve for A. terreus. A linear biomass growth observed also by Bizukojc and Ledakowicz [8][9][10] and Pawlak and Bizukojc [57] seems to be untypical. Lack of typical exponential phase may make it difficult to model A. terreus growth as the existence of this phase is often assumed in the kinetic models, including the ones described above.…”
Section: Linear Growth Of Biomass In a Terreus Returning To Fungal mentioning
confidence: 71%
See 4 more Smart Citations
“…All in all, it is unlikely to find in literature the exponential growth curve for A. terreus. A linear biomass growth observed also by Bizukojc and Ledakowicz [8][9][10] and Pawlak and Bizukojc [57] seems to be untypical. Lack of typical exponential phase may make it difficult to model A. terreus growth as the existence of this phase is often assumed in the kinetic models, including the ones described above.…”
Section: Linear Growth Of Biomass In a Terreus Returning To Fungal mentioning
confidence: 71%
“…Lack of typical exponential phase may make it difficult to model A. terreus growth as the existence of this phase is often assumed in the kinetic models, including the ones described above. A closer look to this phenomenon was made by Pawlak and Bizukojc [57]. They thoroughly studied the very early stages of A. terreus growth in the shake flask culture and found that the exponential growth phase lasted not longer than 12 h since the inoculation with the 24-h preculture (Fig.…”
Section: Linear Growth Of Biomass In a Terreus Returning To Fungal mentioning
confidence: 86%
See 3 more Smart Citations